Interaction of In-Between Spaces in University Campuses with Informal Learning and Spatial Design: a Scoping Review - Akkurt, Ezgi; Akbulut, Muzaffer Tolga (Taylor & Francis, 2025)
The design of learning spaces on 21st-century university campuses significantly contributes to learning and socialization by addressing diverse student needs. Beyond formal, dedicated learning environments, in-between spaces – which support individual study, collaborative discussions, and social interactions – are gaining importance. These spaces foster informal learning and enhance a sense of community among students by facilitating social connections. This scoping review investigates how in-between spaces on university campuses support informal learning and social interaction by examining literature to identify trends, knowledge gaps, and effective spatial design strategies beyond formal education. This scoping review was conducted following Arksey and O’Malley’s methodological framework and adhered to PRISMA-ScR reporting guidelines. It synthesized findings from 14 selected studies, analyzing how in-between spaces contributed to informal learning processes and spatial design on university campuses. The review specifically targeted literature published between 2000 and 2025, reflecting significant developments in educational paradigms, digital transformation, and evolving spatial requirements in higher education. This timeframe was deliberately chosen to capture the dynamic context of contemporary learning environments increasingly characterized by informal and adaptable spatial approaches. This review offers theoretical insights and evaluation criteria to guide campus planning by clarifying the functional roles of in-between spaces in informal learning and social interaction.
Keywords: In-Between Space; Informal Learning; University Campuses; Data Measurements; Scoping Review